2019
DOI: 10.1097/cce.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Cardiovascular Data Sampling Frequency and Referencing It to Baseline Improve Hemorrhage Detection

Abstract: Objectives: We hypothesize that knowledge of a stable personalized baseline state and increased data sampling frequency would markedly improve the ability to detect progressive hypovolemia during hemorrhage earlier and with a lower false positive rate than when using less granular data. Design: Prospective temporal challenge. Setting: Large animal research laboratory, University Medical Center. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Following lung function, like looking for signatures of illness, in our view requires continuous recording of organ function: the more highly resolved, the better. Pinsky et al recently demonstrated the additional information of noninvasive and invasive heart rate and waveform data in early detection of hemorrhage in pigs ( 68 , 69 ), affirming clinical studies ( 45 , 70 ). Heart rate analysis is directly applicable to clinical practice—each heartbeat sends an easily detected signal and allows for detailed analysis of long time-series of interbeat intervals using new and old mathematics ( 71 , 72 ).…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Following lung function, like looking for signatures of illness, in our view requires continuous recording of organ function: the more highly resolved, the better. Pinsky et al recently demonstrated the additional information of noninvasive and invasive heart rate and waveform data in early detection of hemorrhage in pigs ( 68 , 69 ), affirming clinical studies ( 45 , 70 ). Heart rate analysis is directly applicable to clinical practice—each heartbeat sends an easily detected signal and allows for detailed analysis of long time-series of interbeat intervals using new and old mathematics ( 71 , 72 ).…”
mentioning
confidence: 81%
“…1) Predictive analytics monitoring for clinical decision support for rapidly moving illnesses should incorporate continuous cardiorespiratory monitoring in the ICU and on the floor when it is available, because it adds information to nurse-charted vital signs and laboratory tests ( 45 , 68 70 ).…”
mentioning
confidence: 99%
“…Graphical features include the amplitude and time domain features extracted from PPG and ABP, and their first derivative waveform has been widely used for tracking hemodynamics [ 21 , 22 ]. Our previous studies also attempted to use features derived from vital signs and machine learning techniques to detect hemorrhage and reported the ability of PPG-waveform-derived features, heart rate, and BP-derived features in reflecting physiological condition changes in subjects suffering from blood loss [ 18 , 23 , 24 ]. Similar features were extracted as the feature metrics in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The indigenous physiological variability among the patients in the training data can lead to harmful effects on the generalizability of the trained model on previously unseen patients. Reference to a personal baseline collected during the patients' stable state can greatly help reduce the detrimental effects of heterogeneity among the patients and improve the performance of the downstream machine learning models [13][14][15]. However, for patients presenting in already acute states, e.g., trauma patients rushed in for care, there is no such luxury of observing the patients' personal baseline information when they were stable.…”
Section: Introductionmentioning
confidence: 99%